Mechanical Properties of Nanocomposites Reinforced by Polyamide 66 Nanofibers - sabah, Reyam; Jabbar, Zuhair; Jawad, Hanaa (International Journal of Engineering and Technology, 2018)
Mechanical properties of the polyamide 66 nanofibers / epoxy nanocomposite, involved (tensile strength, impact strength, and hardiness) were tested. Four samples of nanocomposites were prepared involved (pure epoxy, epoxy with pure polyamide nanofibers, epoxy with (nanofibers + 0.02 wt.% Alumina nanoparticles ), and epoxy with (nanofibers + 0.03 wt.% Alumina nanoparticles). Nanofibers of nylon66 prepared by electrospinning technique by dissolve (3g) of nylon66 in (17 ml) of formic acid. Nanofiber mixed with epoxy resin by (0.03) wt%. Results show there are an enhancement of mechanical properties of nanofibers nanocomposites, which prepared especially impact strength. On the other hand, the addition of alumina nanoparticles leads to more enhancement of impact strength of nanocomposites.Â
Keywords: Mechanical properties; Nanofiber; Nylon 66; Electrospinning; Nanocomposite; and aluminum oxide.